2021
DOI: 10.1039/d0ra08672j
|View full text |Cite
|
Sign up to set email alerts
|

Thriving artificial underwater drag-reduction materials inspired from aquatic animals: progresses and challenges

Abstract: In the past decades, drag-reduction surfaces have attracted more and more attention due to their potentiality and wide applications in various fields such as traffic, energy transportation, agriculture, textile industry, and military.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 203 publications
0
26
0
Order By: Relevance
“…The mucus on the body gives the fish a slippery sensation with excellent drag reduction. [61] Rong et al also mimicked fish scale micro/ nanostructure arrays and fabricated a sample by laser ablation that provided hydrophobic and drag-reducing properties. [65] The body surface of the puffer has evolved spiky structures that are distinct from the scales in other fish species, as shown in Figure 5.…”
Section: Epidermal Microstructures Of Other Underwater Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mucus on the body gives the fish a slippery sensation with excellent drag reduction. [61] Rong et al also mimicked fish scale micro/ nanostructure arrays and fabricated a sample by laser ablation that provided hydrophobic and drag-reducing properties. [65] The body surface of the puffer has evolved spiky structures that are distinct from the scales in other fish species, as shown in Figure 5.…”
Section: Epidermal Microstructures Of Other Underwater Animalsmentioning
confidence: 99%
“…“Bearing” has been interpreted as changing the sliding friction between the fluid and wall into rolling friction between fluid and fluid, resulting in less surface drag. [ 61 ] At the same time, the existence of vortices will cause a partial slip of the fluid as it flows through the microstructured surface, and the drag reduction mechanism of the partial slip of the fluid will be introduced later. The existence of the groove generates vortices along the flow direction and pushes the high turbulent kinetic energy region away from the groove surface.…”
Section: Drag Reduction Microstructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Wen et al (2014) noted in their flexible three-dimensional (3D) printed shark skin research that around 7% drag could be possible. Likewise, when shark skin mimicked microchips made of sensors, actuators and electronics showed that drag reduction of 8% is feasible (Tian et al , 2021). These ample amounts of drag reduction have attracted many researchers and hence Liang et al (2019) done their research based on 3D-printed shark skin-like structures and noted that viscous drag could be reduced up to 9%.…”
Section: Introductionmentioning
confidence: 99%
“…Fish skin is a part of the first line of defence that acts as an envelope protecting it from injury and environmental insult. Skin plays an important role in various activities such as respiration, excretion, osmoregulation and friction reduction (Tian et al, 2021). Cutaneous diseases are relatively more common in fish than in terrestrial vertebrates as the fish is continuously immersed in an aquatic environment (Groff, 2001).…”
mentioning
confidence: 99%